2015
DOI: 10.1371/journal.pone.0118568
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing the Diagnostic Accuracy of Visual Inspection with Acetic Acid to Visual Inspection with Lugol’s Iodine for Cervical Cancer Screening in HIV-Infected Women

Abstract: Visual inspection with Acetic Acid (VIA) and Visual Inspection with Lugol’s Iodine (VILI) are increasingly recommended in various cervical cancer screening protocols in low-resource settings. Although VIA is more widely used, VILI has been advocated as an easier and more specific screening test. VILI has not been well-validated as a stand-alone screening test, compared to VIA or validated for use in HIV-infected women. We carried out a randomized clinical trial to compare the diagnostic accuracy of VIA and VIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
(27 reference statements)
1
22
0
1
Order By: Relevance
“…Previous studies comparing the performance of VIA to visual inspection with Lugol’s iodine (VILI) found similar diagnostic accuracy and rates of CIN2+ detection (30, 31); however, no studies have been conducted that assess the additive diagnostic accuracy of VIA + VILI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies comparing the performance of VIA to visual inspection with Lugol’s iodine (VILI) found similar diagnostic accuracy and rates of CIN2+ detection (30, 31); however, no studies have been conducted that assess the additive diagnostic accuracy of VIA + VILI.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the addition of Lugol's iodine as a secondary contrast agent improved the agreement between the two colposcopes for all pathological categories by 8.9% and the accuracy of physician interpretation compared with pathology by 5.6 and 9.2% for the Pocket and standard-ofcare colposcopes, respectively. Previous studies comparing the performance of VIA with visual inspection with Lugol's iodine (VILI) found similar diagnostic accuracy and rates of CIN2+ detection; 30,31 however, no studies have been conducted that assess the additive diagnostic accuracy of VIA + VILI.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Similarly studies done in some other Africa countries like Egypt and Kenya revealed higher level of sensitivity of VIA. [23,30] Though, histology was not done in our study, but this is significantly high enough to validate VIA in a criterion validity. A specificity of 91.2% in a criterion validity study shows that there is an appreciable agreement between the study screening test (VIA) and the gold standard (Pap smear) in addition to the fact that VIA was able to pick 100% of HGSIL detected with Papanicolaou smear.…”
Section: Discussionmentioning
confidence: 87%
“…The most commonly used screening methods include conventional cervical cytology (Pap smears), hrHPV testing, and visual inspection with acetic acid (VIA). Several studies have evaluated the performance of these methods in WLWH [114][115][116][117][118][119][120][121][122][123][124][125]. Generally, hrHPV DNA testing is the most sensitive method for detecting CIN2+ lesions (range 89-95%), followed by conventional cytology (53-93%) and VIA (48-84%).…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%